Influence of Fixed Carbon Carburizer on The Hardness and Microstructure of Cast Iron FC 25 - Putra, Adi Ganda; Ghose, Aurobindo; Pawawoi; Sukmara, Sony (Yayasan Banu Haji Samsudin, 2023)
Cast iron smelting is carried out with the main materials, namely steel scrap (C) 0.08% and recycled material FC 25 (C) 3.37% so that the mixture of the two raw materials results in the carbon content being less than the FC 25 target which has a content range (C) between 3.10% – 3.40% (JIS G 5501). In order for element (C) to meet the material standardization criteria, a carburizer is used as an addition to element (C) in the smelting process. This research uses an induction furnace with a capacity of 1500 kg for the melting process. Metallographic testing aims to see the comparison of the microstructure that occurs. Brinell hardness testing is carried out by providing 5 point indent traces on the surface. (α) and 2 points in the phase (α+Fe3C). The research results show that the addition of element (C) using a carburizer with a fixed carbon content of 91.57% and 96.7% in casting FC 25 material affects the value of material hardness, phase hardness and microstructure in FC 25 material. The use of carburizers with different contents This does not affect the graphite shape, graphite type and graphite size. The use of a 96.7% carburizer produces a Brinell hardness value of 205 HB, Vickers 259 HV and a pearlite phase percentage of 59% which is higher than a 91.67% carburizer which produces a Brinell hardness value of 184 HB, Vickers 238 HV and a pearlite phase percentage of 56%.